2013
DOI: 10.1097/qai.0b013e31828175c9
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Use and Urinary Biomarkers Among HIV-Infected Women in the Women's Interagency HIV Study (WIHS)

Abstract: Background Tenofovir has been associated with renal tubular injury. Biomarkers that signal early tubular dysfunction are needed because creatinine rise lags behind tenofovir-associated kidney dysfunction. We examined several urinary biomarkers to determine if rises accompanying tenofovir initiation preceded creatinine changes. Methods Three urinary biomarkers of tubular impairment- neutrophil gelatinase-associated lipocalin (NGAL), N-acetyl- β -D-glucosaminidase (NAG), and β-2-microglobulin (β2MG)-were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…Changes in its urinary and plasmatic concentrations have been used to implicate kidney dysfunction and tubulopathy [40,41]. NGAL is produced by neutrophils and its urinary level is considered a marker of kidney injury [42,43]. β2-Microglobulin is a small protein located in all nucleated cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in its urinary and plasmatic concentrations have been used to implicate kidney dysfunction and tubulopathy [40,41]. NGAL is produced by neutrophils and its urinary level is considered a marker of kidney injury [42,43]. β2-Microglobulin is a small protein located in all nucleated cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the known mechanisms of TDF renal toxicity are expressed in the proximal tubule, new markers of tubular dysfunction such as neutrophil gelatinase associated lipocalin (NGAL) could be used to early detect a TDF related kidney damage, although the results of the few studies using NGAL as a biomarker of tubular damage in HIV patients have reported contrasting results [67][68][69][70]. There is lack of knowledge on the topic in HBV-infected patients [68].…”
Section: Tdf Dose Adjustmentmentioning
confidence: 98%
“…In this study, renal impairment and PRTD began to improve as early as three months after discontinuation of nucleotide analogue as seen from the rising TmPO 4 /GFR representing improved tubular reabsorption of phosphate and the declining 24-hour urinary protein and urinary 2-microglobulin, which is a 12 kDA tubular protein with a component of major histocompatibility complex class I molecule [32]. Urinary 2-microglobulin is known to be a specific marker of proximal renal tubular dysfunction, which has been studied in HIV patients who developed antiretroviral agents related to PRTD [28,[32][33][34]. The rapid decline of renal losses of urinary protein and 2-microglobulin after cessation of nucleotide analogue signified the restoration of proximal renal tubular structure and function.…”
Section: Discussionmentioning
confidence: 99%